Diskon dan Kualitas Pelayanan sebagai Penentu Kepuasan Pelanggan - Valentino, Yonathan Hervan; Lu, Cen (Teewan Journal Solutions, 2026)
This research aims to investigate the impact of discounts and service standards on customer satisfaction levels at Maranatha Store, a retail business operating in the area of Maranatha Christian University. In the face of increasingly fierce retail competition, ensuring customer satisfaction is crucial for maintaining consumer loyalty, especially among students who are a key target market. This research uses a quantitative approach with a survey method, distributing questionnaires to 126 respondents who are active students who have shopped directly at Maranatha Store. The sampling method used is purposive sampling. The collected data was analyzed using multiple linear regression with the help of SPSS software version 25. The findings of this study indicate that discounts have a positive and significant impact on customer satisfaction, and service quality also has a positive and significant impact on customer satisfaction. Simultaneously, discounts and service quality were found to have a significant impact on customer satisfaction. These results indicate that the right discount strategies and continuous improvement in service quality can enhance customers' perceived value and shopping experience. This research is expected to serve as a managerial reference for Maranatha Store in designing more effective marketing and service strategies, and to contribute to the development of studies on retail marketing within the campus environment.